Sinopse de Poaceae do Parque Nacional do Iguaçu, Paraná - Brasil - Brito, Luciely Fernanda Prudencio de (2024)
Poaceae is one of the largest families among angiosperms, present in all ecosystems, and with many species in the Atlantic Forest. In Brazil, the family is represented by 1,551 species belonging to 232 genera, of which 510 are considered endemic to the country. The Iguaçu National Park (ParNa Iguaçu) is home to one of the largest remnants of the interior Atlantic Forest, with Mixed Ombrophylous Forest (MOF) and Semideciduous Seasonal Forest (SSF). The objective of this work was to prepare a synopsis of Poaceae from the Iguaçu National Park, presenting an identification key and the way in which these species are distributed in the different areas and vegetation types of the Park. To this end, collections have been carried out since 2015, and intensified from May 2019 to February 2020, with monthly collections. Trails were followed in different municipalities that make up ParNa Iguaçu, seeking to cover the different regions of the park in terms of vegetation formations and altitude. Consultations were also carried out on the computerized collection available on the Species Link network (http://inct.splink.org.br) and JABOT (http://jabot.jbrj.gov.br) to verify records of the occurrence of Poaceae species in the ParNA Iguaçu. 70 species were found distributed in 40 genera. Among the most representative genera are Paspalum (10 spp.), Setaria (5 spp.) and Olyra (4 spp.), followed by Digitaria and Panicum with three species each and Cenchrus, Chloris, Chusquea, Dichanthelium, Eleusine, Hildaeae, Hymenachne, Steinchisma and Urochloa with two species each, and the other genera with one species each. The present survey significantly expanded the number of Poaceae species for the park, and of Poaceae species indicated as occurring in Semideciduous Seasonal Forest. It also revealed a new occurrence in Paraná.